2010
DOI: 10.1111/j.1600-0765.2009.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 mediates nicotine- and lipopolysaccharide-induced expression of cyclooxygenase-2 and inducible nitric oxide synthase in human periodontal ligament cells

Abstract: Our data suggest that the nicotine- and LPS-induced inflammatory effects on PDL cells may act through a novel mechanism involving the action of HO-1. Thus, HO-1 may provide a potential therapeutic target for the treatment of periodontal disease associated with smoking and dental plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 36 publications
4
44
0
Order By: Relevance
“…Inflammation cytokines and mediators, such as IL-1b and PGE 2 , are well known to be involved in mechanical stretch-induced inflammation in articular tissues [24][25][26][27]. For example, mechanical stretch was found to enhance the production of PGE 2 and its related enzyme COX-2 in skeletal muscle cells, while it also induced IL-1b expression in cardiac muscle cells [28, It is well known that HO-1 is a stress-induced isoform of heme oxygenases that also has anti-inflammatory functions [17][18][19]. Furthermore, HO-1 is thought to be rapidly induced with oxidative stress and to act as a potent endogenous factor for resolution of stress-induced inflammatory injury [17,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation cytokines and mediators, such as IL-1b and PGE 2 , are well known to be involved in mechanical stretch-induced inflammation in articular tissues [24][25][26][27]. For example, mechanical stretch was found to enhance the production of PGE 2 and its related enzyme COX-2 in skeletal muscle cells, while it also induced IL-1b expression in cardiac muscle cells [28, It is well known that HO-1 is a stress-induced isoform of heme oxygenases that also has anti-inflammatory functions [17][18][19]. Furthermore, HO-1 is thought to be rapidly induced with oxidative stress and to act as a potent endogenous factor for resolution of stress-induced inflammatory injury [17,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Wagner et al reported that hemodynamic forces induce HO-1 expression in vascular smooth muscle cells, indicating that normal arterial levels of shear stress selectively induce HO-1 gene expression [16]. Although HO-1 only protects against oxidative stress, it has received a great deal of attention in regard to its potent anti-inflammatory functions [17][18][19]. On the other hand, the mechanism by which HO-1 suppresses inflammatory responses induced by mechanical stretch in synovial cells remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that nicotine and LPS synergistically induce the production of nitric oxide (NO) and PGE 2 , and increase inducible nitric oxide synthase (iNOS) and COX-2 expression in human periodontal ligament (hPDL) cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that the HO-1 pathway is a key mechanism for both the adaptation of cells to stressful conditions and their recovery from injurious events in human pulp and PDL cells [27][28][29][30][31][32]. Moreover, HO-1 has therapeutic potential in hepatoprotection [33], inflammatory arthritis [34], psoriasiform skin lesions [35], neuroinflammation [36], inflammatory bowel disease [37], and periodontitis [15]. In our previous study [15], the inhibition of HO-1 in LPS-and nicotine-stimulated human PDL cells resulted in the suppression of iNOS and COX-2 expression, as well as a reduction in NO and PGE 2 levels.…”
Section: Introductionmentioning
confidence: 99%
“…It also stimulates the formation of osteoclast-like cells by increasing macrophage colony-stimulating factor and PGE2 production in osteoblasts [215]. Nicotine and LPS synergistically induced the production of nitric oxide and PGE2, and increased the expression of inducible nitric oxide synthase (iNOS) and COX-2 via heme oxygenase-1 in PDLCs [216]. From these studies, it is evident that the pro-inflammatory potential of P. gingivalis is reduced in the presence of nicotine.…”
Section: 9c Cigarette Smoke and P Gingivalismentioning
confidence: 96%